Gastric perforation secondary to a trichobezoar: A case report and review of the literature - Gayatri Malhotra-Gupta, DO; Courtney Janowski, MD; Richard Sidlow, MD (Elsevier, 2017)
This paper describes a 10-year-old female in whom gastric perforation occured secondary to a massive gastric trichobezoar. A literature review of this rare cause of gastric perforation follows.